Handbuch Satz, Äußerung, Schema - Dürscheid, Christa,Schneider, Jan Georg (De Gruyter, 2015)
Clear and concisely written, this series provides comprehensive insight into linguistic interrelationships. Each volume addresses a different linguistic phenomenon, rather than being devoted to a specific subfield. Beyond providing systematic descriptions, the series addresses historical as well as social language configurations, normative public opinion, and the significance of linguistic phenomena in key domains of knowledge and human activity.
Description based on publisher supplied metadata and other sources
Keywords: Satz; Äußerung; Syntax; Sprachsystem; Sprachgebrauch